Analisis Buku Ajar Bahasa Arab Al- Arabiya Li Al-Najah Menurut Perspektif William Frances Mackey - Mirwan Ahmad Taufiq; Ainur Ridho; Arum Kusmila Surya Putri (Jurnal Pendidikan Bahasa Arab, 2023)
The textbook plays a strategic role in achieving the curriculum, therefore it needs to be prepared systematically and integrated with the development, planning, and evaluation processes. Analysis of textbooks is very important to determine the quality of the textbook itself. The purpose of this study is to determine the quality of the Al-Arabiyah li Al-Najah textbook according to William Frences Mackey's assessment standards. This research was conducted using a descriptive qualitative method and content analysis techniques from the perspective of William Frences Mackey. The primary data source in this study was taken from the Al-Arabiyah li Al-Najah textbook, while secondary data sources came from relevant books, articles, and readings related to the research object. The results of this study indicate that the Al-Arabiyah li Al-Najah textbook has met four standards formulated by William Frences Mackey, namely material selection, gradation, presentation, and repetition aspects.